Butterflies of Pench Tiger Reserve, Madhya Pradesh, India - Tiwari, Umesh Kumar L.; Jena, Jyotirmay; Dungriyal, N. S. (Indian Forester, 2010)
Rich butterfly fauna was found in Pench Tiger Reserve (Area 757.904 Km2) which include a total of 126 butterfly species belonging to 74 genera and 5 families. Family Nymphalidae was dominant with 51 species belonging to 23 genera followed by Lycanidae with 37 species in 25 general, Hesperidae and Pieridae with 16 and 14 species respectively and Papilionidae was represented by only 8 species.